Information seeking behaviour of agricultural enginneers in Nigeria: institutional influences, information sources and channels (2000)
This study sought to determine the information seeking behaviour of agricultural engineers in Nigeria. There was also an interest in funding out if they differed in their information seeking behaviour according to their different places to work. It made use of 261 agricultural engineers who were selected from the different organisations where they work by stratified random sampling. Data collection invovled the use of the questionnaire while data analysis invovled the use of analysis of variance statistics (for independent groups). The result shows that majority of the agricultural enginneers search for information by use of traditional print sources (journals textbooks etc.) On -line sources of information were no popular with the enginneers. The result also show that the agricultural engineers differed in thier information seeking behaviour according to their different palces of work. Recommendations include the supply of current information sources to their different organisations and training facilities as regards computer on-line search for information.